FEATURES OF THE PREVALENCE OF ALLERGY OF DUST AND EPIDERMAL ETIOLOGY AMONG THE CHILDREN OF THE RURAL POPULATION OF THE LIVESTOCK-BREEDING AREA (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In the Farish district of the Jizzakh area of the Republic of Uzbekistan, children who live among cattle are studied for the incidence of dust and epidermal allergies.